Laser-assisted production of HAp-coated zirconia structured surfaces for biomedical applications. (December 2020) - Faria, D.; Henriques, B.; Souza, A.C.; Silva, F.S.; Carvalho, O.
Abstract: Objectives: The aim of this study was to develop a novel design for implants surface functionalization through the production of HAp-coated zirconia structured surfaces by means of hybrid laser technique. The HAp-rich structured surfaces were designed to avoid hydroxyapatite (HAp) coating detachment from the zirconia surface during implant insertion, thus guaranteeing an effective osseointegration. Materials and methods: The functionalization process of zirconia surface started by creating micro-textures using a Nd:YAG laser and subsequent deposition of a HAp coating on the designated locations by dip-coating process. Afterwards, a CO2 laser was used to sinter the HAp coating. The potential of the HAp-coated zirconia structured surfaces was inspected concerning HAp bioactivity preservation, surface wettability, HAp coating adhesion to the textured surfaces and mechanical resistance of zirconia, as assessed by different approaches. Results: The functionalized surfaces exhibited a superhydrophilic behavior (2.30 ± 0.81°) and the remaining results showed that through the hybrid strategy, it is possible to maintain the HAp bioactivity as well as promote a strong adhesion of HAp coating to the textured surfaces even after high energy ultrasonic cavitation tests and friction tests against bovine bone. It was also verified that the flexural strength of zirconia (503 ± 24 MPa) fulfills the strict requirements of the ISO 13356:2008 standard and as such is expectable to be enough for biomedical applications. Significance: The promising results of this study indicate that the proposed surface design can open the window for manufacturing zirconia-based implants with improved bioactivity required for an effective osseointegration as it avoids the coating detachment problem during the implant insertion.